Analisis Penghapusan Presidential Threshold Berdasarkan Putusan MK No. 62/PUU-XXII/2024 dalam Penguatan Hak Politik sebagai Hak Konstitusional Warga Negara - Agsel Awanisa (Jurnal Hukum Lex Generalis, 2025)
The presidential threshold provision in Article 222 of Law Number 7 of 2017 concerning General Elections has been upheld by the Constitutional Court through the rejection of 33 judicial review petitions on the grounds that it is an open legal policy of the legislature. However, Constitutional Court Decision Number 62/PUU-XXII/2024, which abolished the presidential threshold provision, marked a change in the constitutional paradigm in the practice of electoral democracy in Indonesia. This study aims to analyze political rights as constitutional rights and examine the implications of this decision on strengthening the political rights of citizens. The research method used is normative legal research with a conceptual approach and a statutory approach. The results of the study show that the right to vote and be elected are human rights guaranteed by the 1945 Constitution of the Republic of Indonesia as fundamental constitutional rights that must be recognized, respected, and fulfilled by the state. Constitutional Court Decision No. 62/PUU-XXII/2024 opens up a more inclusive space for political parties participating in elections to nominate presidential and vice-presidential candidates, thereby expanding political choices for voters through a more fair and open contest. The novelty of this research lies in the analysis of the shift in the Constitutional Court's constitutional stance from the open legal policy doctrine in 33 previous decisions to an approach that places political rights as constitutional rights that must be prioritized in a democratic electoral system. This finding strengthens the argument that the elimination of the presidential threshold is in line with the principles of constitutional democracy and the protection of citizens' political rights.